Two mutations in the hormone binding domain of the vitamin D receptor cause tissue resistance to 1,25 dihydroxyvitamin D3. - Kristjansson, K (1993)
We have identified and characterized two mutations in the hormone binding domain of the vitamin D receptor (VDR) in patients with hereditary vitamin D-resistant rickets. One patient was found to have a premature stop mutation (CAG to TAG) in the hinge region affecting amino acid 149 (Q149X) and the other demonstrated a missense mutation (CGC to CTC) resulting in the substitution of arginine 271 by leucine (R271L) in the steroid binding domain. Eukaryotic expression analyses in CV-1 cells showed the inability of both patients' VDR to induce transcription from the osteocalcin hormone gene response element at 10(-7) M 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). Normal transcription levels could, however, be elicited by the missense mutated VDR (R271L) in the presence of 1,000-fold higher 1,25-(OH)2D3 concentrations than needed for the wild-type receptor. This shows that Arg 271 directly affects the affinity of the VDR for its ligand and its conversion to leucine decreases its affinity for 1,25(OH)2D3 by a factor of 1,000. Arg 271 is located immediately 3-prime to a 30 amino acid segment (VDR amino acids 241-270) that is conserved among members of the steroid/thyroid/retinoid hormone receptor superfamily. These results represent the first missense mutation identified in the hormone binding domain of VDR and further define the structure-function relationship of 1,25(OH)2D3 ligand binding to its nuclear receptor.